ANALYSIS OF LOAD AND WORK ENVIRONMENT FOR OPTIMIZATION OF HUMAN RESOURCES (HR) - Apriyando, Muhammad; Reovaldy, Rafif; Yatun, Rohmi; Lestari, Eva; Hadiati, Eti; Elice, Deti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Structured planning is an essential element in achieving goals, both at the individual and organizational levels. With good planning, strategic steps can be formulated to ensure the achievement of goals effectively and efficiently. In the context of the organization, human resource planning (HR) plays a strategic role in ensuring the availability of manpower in accordance with operational needs. This process includes workload and workforce analysis to determine ideal workforce needs and improve organizational operational efficiency. This study uses a research methodology (library research), which is a way to obtain data by knowing and studying theories from various literature related to research. However, many organizations face challenges in effectively integrating such analytics into HR management. These constraints often impact employee productivity, task distribution, and well-being. Therefore, it is important to understand the factors that affect the effectiveness of HR planning, especially related to workload and work environment conditions. This study aims to evaluate the influence of workload variables and work environment on work security and its impact on employee stress levels. Using the literature review method, this study identified the mismatch between workload and individual capacity and a less conducive work environment as the main cause of increased work stress. Factors such as excessive work duration and uncomfortable environmental conditions contribute to high work pressure. The findings of this study provide important insights for organizations in designing appropriate interventions, such as optimizing workload distribution and improving work environment conditions. With these measures, organizations can improve employee well-being, reduce stress levels, and encourage overall workforce productivity